Analisis Kebijakan Pembiayaan Publik: Makna Strategis APBN dalam pembangunan Ibu Kota Nusantara - Tiara Marsya Aulya; Nayla Ahlami Dalimunthe; Cintya Putri Nasution; Dia Aulia Harahap; Suaini Mebia Putri (EKALAYA : Jurnal Ekonomi Akuntansi, 2025)
This article examines the strategic role of Indonesia’s State Budget (APBN) in financing the development of the new capital city, Ibu Kota Nusantara (IKN). The scope of the discussion focuses on public financing policy, the fiscal rationale behind state-led investment, and the position of APBN in securing the early stages of national strategic projects. The study employs a qualitative research design using a document analysis approach to review official government sources, including the APBN, fiscal policy statements, planning documents for IKN, and publications issued by the Ministry of Finance, Bappenas, and the IKN Authority. The analysis reveals that APBN serves as the dominant and foundational instrument in the initial development phase, functioning not only as a direct funding source but also as a stabilizing mechanism that signals long-term governmental commitment. The findings further show that APBN operates as a trigger to attract non-budget financing by preparing essential infrastructure and reducing early-stage investment risks. However, the study also identifies potential fiscal pressures and governance challenges if diversification of financing does not progress as planned. Overall, the research highlights that APBN plays a strategic and multidimensional role in shaping the direction, credibility, and sustainability of IKN development.